The Buoy Effect: Surface Enrichment of a Pt Complex in IL Solution by Ligand Design. Issue 3 (4th January 2023) - Hemmeter, Daniel; Kremitzl, Daniel; Schulz, Peter S.; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans‐Peter
Abstract: Invited for the cover of this issue are the groups of Hans‐Peter Steinrück and Peter Wasserscheid at the Friedrich‐Alexander‐Universität Erlangen‐Nürnberg. The image depicts two Pt catalysts dissolved in an ionic liquid. For one of them, fluorinated side chains in the ligand system act as buoys leading to pronounced enrichment of the complex at the gas/IL interface, as is evidenced by strongly enhanced Pt signals in angle‐resolved photoelectron spectroscopy. For the complex without fluorinated side chains, no such effect is observed. Read the full text of the article at 10.1002/chem.202203325 . Abstract : " The accumulation of the catalyst at the gas/IL interface is even more pronounced than expected from the surface activity of the free ligand ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202203325 ).